THE INFLUENCE OF PHYSICAL FITNESS OF GIRLS 11-15 YEARS OLD WITH POSTURAL DISORDERS ON THE FORMATION OF MOVEMENT CULTURE - Vasylchuk, Hryhoriy (Mountain School of Ukrainian Carpaty, 2022)
The article examines the peculiarities of the level of physical fitness of girls aged 11-15 who have postural disorders. A comparative characterization of the indicators of motor readiness of girls with and without postural disorders was also carried out. The influence of motor activity on the formation of correct posture and improvement of physical health was studied. The content of the concept of "posture disorders" was analyzed and it was established that posture is an important comprehensive indicator of the state of health and harmonious physical development of each person. And the correct posture ensures an optimal position and normal activity of internal organs, creating the best conditions for the activity of the entire body. It was determined that the physical fitness indicators of girls with postural disorders are significantly lower than those of their peers without postural disorders. The main reasons that contribute to the development of hypodynamism among schoolchildren, which negatively affects their posture, have been clarified. A reliable difference was established between the level of physical fitness of elementary school students with different posture development. It is emphasized that options for solving this problem are possible due to the intensive use of all means of physical culture. It was concluded that the majority of elementary school students have a sedentary lifestyle, which negatively affects their psycho-emotional and somatic state, and as a result, low and moderate physical fitness is observed. Therefore, this problem requires the search for new ways and methods of prevention and elimination of damaged locomotor apparatus during the child's development, taking into account their physical fitness, mortality, anthropometric, psychological and individual characteristics. Keywords: physical education, schoolgirls, primary school, posture disorders, physical fitness.